2023
DOI: 10.1021/acs.est.2c06556
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Cross-Over Study of In-Vehicle Cabin Air Filtration, Air Pollution Exposure, and Acute Changes to Heart Rate Variability, Saliva Cortisol, and Cognitive Function

Abstract: To determine how traffic-related air pollution (TRAP) exposures affect commuter health, and whether cabin air filtration (CAF) can mitigate exposures, we conducted a cross-over study of 48 adults exposed to TRAP during two commutes with and without CAF. Measurements included particulate air pollutants (PM 2.5 , black carbon [BC], ultrafine particles [UFPs]), volatile organic compounds, and nitrogen dioxide. We measured participants' heart rate variability (HRV), saliva cortisol, and cognitive function. On aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Thus, people with prediabetes or diabetes could be encouraged to use central air conditioning, if accessible and affordable, instead of electric fans and especially instead of opening windows for indoor temperature regulation. The results of a few experimental studies also support the use of in-vehicle air conditioning to reduce air pollution exposure while driving ( 192 194 ).…”
Section: An Eye Toward Preventionmentioning
confidence: 75%
“…Thus, people with prediabetes or diabetes could be encouraged to use central air conditioning, if accessible and affordable, instead of electric fans and especially instead of opening windows for indoor temperature regulation. The results of a few experimental studies also support the use of in-vehicle air conditioning to reduce air pollution exposure while driving ( 192 194 ).…”
Section: An Eye Toward Preventionmentioning
confidence: 75%
“…In addition, adherence to reporting guidelines such as recruitment time and information about time intervals for intervention are unclear. We also found discrepancies between study periods mentioned in the registered protocol (October and November 2014) and published paper (October and November 2015) …”
mentioning
confidence: 80%
“…We also found discrepancies between study periods mentioned in the registered protocol (October and November 2014) 2 and published paper (October and November 2015). 1 In conclusion, the study by Mallach et al provides insights into cabin air filtration, but we consider that the reporting of results may not follow a standard in RCT such as CONSORT. 5 We hope randomized studies in environmental sciences will be reported in accordance with the standard.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Instead, they designed high-efficiency filters that were highly effective at reducing in-cabin UFP (93% reduction) compared with standard filters (35%–70% reduction). Mallach et al 22 studied the effect of commercially available in-cabin electrostatic air filters compared with sham filters on HRV using a randomized, double-blind, crossover design. Healthy adult participants were driven through Montreal morning traffic.…”
Section: Personal Strategies To Protect the Cardiovascular System Fro...mentioning
confidence: 99%